PENGARUH MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PUSAT KESEHATAN MASYARAKAT (PUSKESMAS) PARIGI KECAMATAN PARIGI KABUPATEN PARIGI MOUTONG - Wulandari, Wulandari (Katalogis, 2018)
Puskesmas parigi is one of the government in in parigi district parigi moutong.To aim for a healthier satisfactory optimal for patients health effort requires good service given employees, therefore prosecuted high performance on those of the employees.High performance on those will be achieved, when in which is motivation.The aims to understand work motivation for the employee performance at community parigi in parigi district parigi moutong, and to know how major motivation work against the employee performance puskesmas parigi in parigi district parigi moutong. Based on analysis by using a statistical technique using 38 the responeden in civil servants the results motivation work that affect the employee performance for puskesmas parigi in parigi district parigi moutong and how major has been set at 77,2 %.